A completive survey study on the feasibility and adaptation of EVs in Beijing, China. (1st February 2017) - Sun, Lishan; Huang, Yuchen; Liu, Shuli; Chen, Yanyan; Yao, Liya; Kashyap, Anil
Highlights: EVs have been greatly developed with a series of encouraging policies. The maxi mileages and braking performance still needs further improvement. More residential and public charging piles should be in the plan and design. APP oriented information of charging station need to be researched and developed. Abstract: The private motor vehicles are significantly important means of transportation in modern lifestyle, however, these also contribute to a large proportion of the total air pollution and primary energy consumption. In order to develop green transportation system, it becomes imperative to use integrated technologies to achieve reduced emissions and utilize renewable energy. Electric vehicles (EVs) have been considered as one of these technologies to transform the traditional vehicle mix. However, the uptake of EV has been debated on factors like cost, performance (autonomous mileage), charging point infrastructure construction, energy saving, policy and end users' adaptation. Present study investigates the technology feasibility (which usually refer to EVs' cost, EV charging, supplier's customer services quality, EV travel performance) and users' adaptation of EV in Beijing, which is a key driver for the EV uptake into the Beijing transportation system. The relevant data have been collected and analyzed in the form of questionnaire survey around all of these factors. While considering the user perception and satisfaction, safety of charging and energy bills have also been investigated. According to the data analysis, it has been found the policy of 'No traffic restrictions for EVs' (the traffic restrictions means for certain date, from Monday to Friday the motor vehicles with the last register number of 1 and 6, 2 and 7, 3 and 8, 4 and 9, 5 and 0, are restricted to travel, respectively), the availability of the charging infrastructure and technical support are the most significant factors affecting the users' opinions on using EVs.